BASIC STRUCTURE MODULE BASED ON HYBRID LEARNING : : NEED ANALYSIS FROM THE STUDENT’S PERPECTIVE - Indrawati Pusparini; Endang Setyo Astuti (UIBU, 2019)
The research aims to find out the basic structure module based on hybrid learning needed by the students of Ikip Budi Utomo Malang in learning structure, especially basic structure. The current study was a need analysis which was done in the area of developing making basic structure module based on hybrid learning. The quantitative method were conducted in this research to describe the students’ needs. In collecting the data, the researcher applied questionnaire for the students as the instrument of the research. The data was taken through a questionnaire with given to 45 students who took basic structure course in the 2018-2019 academic year and analyzed quantitatively. The results of this study reveal that the students need a clear goals of basic structure modul based on hybrid learning, the materials in line with the course outline, the assignment and current technology for the teaching and learning process.